Lost in Translation?: Constructing Ancient Roman Martyrs in Baroque Bavaria - Litaker, Noria ca. 20./21. Jh. (Church history, 2020)
Over the course of the early modern period, parish, monastic, and pilgrimage churches across Catholic Europe and beyond eagerly sought to acquire the relics of ancient Roman martyrs excavated from the Eternal City's catacombs. Between 1648 and 1803, the duchy of Bavaria welcomed nearly 350 of these "holy bodies" to its soil. Rather than presenting the remains as fragments, as was common during the medieval period, local communities forged catacomb saint relics into gleaming skeletons and then worked to write hagiographical narratives that made martyrs' lives vivid and memorable to a population unfamiliar with their deeds. Closely examining the construction and material presentation of Bavarian catacomb saints as well as the vitae written for them offers a new vantage point from which to consider how the intellectual movement known as the paleo-Christian revival and the scholarship it produced were received, understood, and then used by Catholic Europeans in an everyday religious context. This article demonstrates that local Bavarian craftsmen, artists, relic decorators, priests, and nuns - along with erudite scholars in Rome - were active in bringing the early Christian church to life and participated in the revival as practitioners and creative scholars in their own right.